Molecular Pathways Bridging Frontotemporal Lobar Degeneration and Psychiatric Disorders - Zanardini, Roberta; Ciani, Miriam; Benussi, Luisa; Ghidoni, Roberta (Frontiers in Aging Neuroscience, 2016)
The overlap of symptoms between neurodegenerative and psychiatric diseases has been reported. Neuropsychiatric alterations are commonly observed in dementia, especially in the behavioral variant of frontotemporal dementia (bvFTD), which is the most common clinical FTD subtype. At the same time, psychiatric disorders, like schizophrenia (SCZ), can display symptoms of dementia, including features of frontal dysfunction with relative sparing of memory. In the present review, we discuss common molecular features in these pathologies with a special focus on FTD. Molecules like Brain Derived Neurotrophic Factor (BDNF) and progranulin are linked to the pathophysiology of both neurodegenerative and psychiatric diseases. In these brain-associated illnesses, the presence of disease-associated variants in BDNF and progranulin (GRN) genes cause a reduction of circulating proteins levels, through alterations in proteins expression or secretion. For these reasons, we believe that prevention and therapy of psychiatric and neurological disorders could be achieved enhancing both BDNF and progranulin levels thanks to drug discovery efforts.